Images of the Last Judgment in Seville: Pacheco, Herrera el Viejo, and the Phenomenological Experience of Fear and Evil - (:unkn) unknown (My University, 2014)
During the early stages of the seventeenth century in Seville, images of the Last Judgment participated in a long artistic tradition of inspiring fear about the impending apocalypse. This thesis focuses on two paintings of the Last Judgment, one by Francisco Pacheco for the church of St. Isabel in 1614 and the other by Francisco Herrera el Viejo for the church of St. Bernardo in 1628. Pacheco was an influential artist and theoretician in the development of Sevillian art, who substantiated the core values of the Counter-Reformation. In a similar way, Herrera's participation in such development was vital because he was one of the first artists to experiment with naturalism in Seville. The Last Judgment paintings by Pacheco and Herrera sought to activate viewers' consciousness and self-assessment on their actions and thus modify their behavior. By interpreting primary sources such as Pacheco's Arte de la Pintura, this thesis investigates the cultural impact of these paintings through phenomenological methods. These methods derive from theoretical materials formulated by Maurice Merleau-Ponty, Louis Lankford, and Paul Ricoeur. The goal of these methods is to describe the experience of fear and evil in response to the Last Judgment paintings by Pacheco and Herrera. The results of this study illustrate the cultural perspective of evil by placing these paintings in relation to other popular and institutional manifestations of religion, particularly the Spanish auto de fé.
Keywords: 17th-Century Seville; Fear and Evil in Art; Francisco Herrera el Viejo; Francisco Pacheco; Last Judgment Art; Phenomenology in Art History